Sequential Product Development and Introduction by Cash-Constrained Start-Ups - Bhaskaran, Sreekumar; Erzurumlu, S. Sinan; Ramachandran, Karthik (Manufacturing and Service Operations Management, 2021)
Problem definition: Firms developing novel and innovative products regularly face a canonical product development and introduction problem: introduce a proven and immediately available product or delay product introduction until the successful development of an advanced version. Academic/practical relevance: Limited access to resources for the development of an advanced version adds another wrinkle to this problem, particularly for cash-constrained start-ups. For such start-ups, the introduction of an on-hand product can generate additional funds to support the development of an advanced product. However, the lower performance of the on-hand product can negatively impact the perception of the firm’s future products and lower future profitability. Methodology: We study the trade-off between revenues that an on-hand product generates for research and development funding and the negative effect it has on future profits. We characterize the optimal introduction timing of the on-hand product as a function of the financial resource constraints, the interdependence between these sequential products and the cost of development. Results: We identify important differences between the optimal product introduction strategies of a start-up and an established firm. Specifically, although it is always optimal for an established firm to accelerate the launch of a better-quality on-hand product, a start-up might find it optimal to delay its launch. The impact of technological failure and different forms of learning on the optimal strategy of the start-up are also explored. We translate our analytical findings into a managerial framework and illustrate these results using examples from the pharmaceutical and medical devices industries.